1995
DOI: 10.3354/meps127213
|View full text |Cite
|
Sign up to set email alerts
|

Influences of riverine humic substances on bacteria, protozoa, phytoplankton, and copepods in a coastal plankton community

Abstract: The effects of additions of humic substances (derived from river water) on bacteria, protozoa, phytoplankton, and copepods in a coastal plankton community from the Skagerrak (west coast of Sweden) were studied in a n enclosure experiment. Bacterial numbers and bacterial production were significantly higher in the humic treatment compared with non-hurnic treatment. Tintinnids and oligotrich chates also attained higher densities in the humic treatment than in non-humic treatment, probably reflecting higher food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 26 publications
3
54
1
Order By: Relevance
“…diatoms and bacteria). Several studies have shown that terrestrial DOC greatly promotes bacteria biomass production which in turn stimulates the growth of heterotrophic dinoflagellates (Carlsson et al, 1995;Purina et al, 2004;Wikner and Andersson, 2012). Thus, in these conditions, allochthonous terrestrial DOC is actively recycled by bacteria and transferred to dinoflagellates which explains, thus, the depleted δ 13 C values observed in the riverdominated samples (Carlsson et al, 1995).…”
Section: Source Of the Pom (> 10 µM) Fractionmentioning
confidence: 80%
“…diatoms and bacteria). Several studies have shown that terrestrial DOC greatly promotes bacteria biomass production which in turn stimulates the growth of heterotrophic dinoflagellates (Carlsson et al, 1995;Purina et al, 2004;Wikner and Andersson, 2012). Thus, in these conditions, allochthonous terrestrial DOC is actively recycled by bacteria and transferred to dinoflagellates which explains, thus, the depleted δ 13 C values observed in the riverdominated samples (Carlsson et al, 1995).…”
Section: Source Of the Pom (> 10 µM) Fractionmentioning
confidence: 80%
“…Total dissolved iron was measured using hydroxylamine HCl and ferrozine on 0.2 m filtered samples, according to Voelker et al (1997). Chl a was measured spectrophotometrically on cells captured on Whatman GF/F glass-fiber filters (Carlsson et al 1995). DOM absorbance spectra (200-800 nm) were obtained using a HP 8453 spectrometer (Agilent) in a 1.0-cm quartz cell with deionized water as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…Utilization of DON without prior mineralization by the microbial food web in the DON treatment may have given an advantage to the dinoflagellates and diatoms over the monads in competition for N. In contrast, it may be indirect effects associated with microbial food web dynamics that explain the higher abundances of dinoflagellates and diatoms in the DON treatment. Some insight into the complexity of the response of phytoplankton communities to DON additions is indicated by the range of responses reported in the literature at both the community level and in single species cultures (Antia et al 1991;Paerl 1991;Carlsson and Granéli 1993;Carlsson et al 1995).…”
Section: Atmospheric Inputs Of Dissolved Organic Nitrogen Stimulate Ementioning
confidence: 99%